2019
DOI: 10.1097/acm.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

S-PACK: A Modular and Modifiable, Comprehensive Predeparture Preparation Curriculum for Global Health Experiences

Abstract: Problem Approximately 25% of trainees participate in a global health elective during their undergraduate or graduate medical education. Increasingly, educators in the United States and international partners are calling for improved predeparture preparation training for global health experiences. Yet, freely available, easily modifiable curricula are rare. Approach Educators who created the Simulation Use for Global Away Rotations (SUGAR) curriculum for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous research has demonstrated unclear results as to the level of training offered to, and required of, residents prior to GH electives. A 2013 survey of US residency training programs found that 66% offered some pre-departure preparation, with 40% of EM programs offering this training [2,3]. Another 2013 study showed that only 15.4% of EM programs offered training for working internationally [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated unclear results as to the level of training offered to, and required of, residents prior to GH electives. A 2013 survey of US residency training programs found that 66% offered some pre-departure preparation, with 40% of EM programs offering this training [2,3]. Another 2013 study showed that only 15.4% of EM programs offered training for working internationally [10].…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of Global Health (GH) has surged over the last two decades. The availability of GH opportunities influences the ranking of medical schools and residency programs for many applicants, and approximately 25% of United States (US) undergraduate and postgraduate trainees complete a GH elective [1][2]. Similarly, 86% of US Emergency Medicine (EM) residents reported having incorporated the availability of GH electives into their residency program ranking decisions [3].…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, we collaborated with the Midwest Consortium of Global Child Health Educators 27,28 to develop an open-access facilitator training package, S-PACK, which incorporates much of this work. 14,29 Knowledge assessment. All residents must pass (³ 80%) an online Medical Knowledge for Service Abroad (MKSA) examination that we created and was peer-reviewed by GH educators at outside institutions and is updated regularly.…”
Section: Predeparture Trainingmentioning
confidence: 99%
“…These collaborations have fostered the sharing of ideas that have improved our GH track and led to innovations that would not have been possible to undertake as a single institution, such as the creation of the SUGARPREP predeparture curricula. 8,9,14,15,28 We have also learned the importance of flexibility in finding creative ways to adapt our GH track as residency requirements, schedules, and the overall landscape of residency education have changed, most recently with the development of the GH Track Passport.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation